Long-Acting Antipsychotic Injections: Prescribing Practices Across BCUHB - Laura Robbins; Vinila Zachariah; Opeyemi Ikuewumi; Raj Sambhi (BJPsych Open, 2025)
Aims: Our aims for this project were to examine how long-acting antipsychotics are prescribed in the various teams (both inpatient, community and specialist services) across BCUHB, with a view to identify any emerging trends, and to compare this with data on efficacy and cost-effectiveness obtained via a systematic search of the available literature.